Preparation method of B-site nickel-doped iron-based perovskite material and application of B-site nickel-doped iron-based perovskite material in medium-temperature solid oxide fuel cell

The preparation of B-position nickel-doped iron-based perovskite material was solved by the EDTA-CA sol gel method, which solved the electrical conductivity and thermal matching problems of the cathode material of medium-temperature solid oxide fuel cell, achieved the improvement of high electrochemical performance and structural stability, and significantly improved the output performance of the battery.

CN120535035AActive Publication Date: 2025-08-26INNER MONGOLIA UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510700793.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-08-26
Estimated Expiration
2045-05-28

AI Technical Summary

Technical Problem

The cathode materials of existing medium-temperature solid oxide fuel cell have low conductivity and poor thermal matching, resulting in poor electrochemical performance and are difficult to use stably under medium-temperature conditions.

Method used

The EDTA-CA sol gel method was used to prepare the iron-based perovskite material La0.6Ca0.4Fe1-xNixO3-δ with B-position doped nickel. By adjusting the molar ratio and pH value of EDTA and CA, the metal ions are uniformly distributed, and the porous structure is formed, and the matching of conductivity and thermal expansion coefficient is improved.

Benefits of technology

The matching of the conductivity and thermal expansion coefficient of the cathode material is significantly improved, the structural stability and electrochemical performance of the battery are enhanced, and the peak power density is increased by 73.61%, much higher than that of the undoped matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535035A_ABST
    Figure CN120535035A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a B-site nickel-doped iron-based perovskite material and application of the B-site nickel-doped iron-based perovskite material in a medium-temperature solid oxide fuel cell, and belongs to the technical field of solid oxide fuel cells. The preparation method of the B-site nickel-doped iron-based perovskite material comprises the following steps: dissolving lanthanum salt, calcium salt, iron salt and nickel salt in water to obtain a metal ion solution; dissolving ethylenediamine tetraacetic acid (EDTA) in a solvent, then mixing with the metal ion solution and citric acid (CA), and adjusting the pH value to be alkaline to obtain a precursor solution; and heating and stirring the precursor solution until the precursor solution becomes a viscous colloid, then evaporating to remove the solvent to obtain precursor powder, and carrying out calcination treatment to obtain the B-site nickel-doped iron-based perovskite material. The La < 0.6 > Ca < 0.4 > Fe < 1-x > Ni < x > O < 3-delta > cathode material with a single perovskite structure is successfully synthesized, has high electrochemical performance and is more suitable for being used as a medium-temperature SOFC (Solid Oxide Fuel Cell) cathode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid oxide fuel cells, and in particular to a preparation method of a B-site nickel-doped iron-based perovskite material and its application in medium-temperature solid oxide fuel cells. Background Art

[0002] Global warming and environmental pollution have become one of the most serious challenges facing the world today, with adverse effects on ecosystems, human health, and socioeconomic development. Solid oxide fuel cells (SOFCs) are known for their ability to convert chemical energy stored in fuels into electrical energy without the need for intermediates. However, the high operating temperature (1000°C) leads to problems such as poor battery durability, high cost, and limited material selection, which restrict the practical application of SOFCs. If the operating temperature of SOFCs can be reduced to an intermediate temperature range of 600-800°C through modification, it will not only broaden the range of material selection but also slow down the rate of performance degradation; however, current related modifications will lead to a decrease in the catalytic activity of the oxygen reduction reaction (ORR) in the cathode material. Therefore, the development of cathode materials with high electrochemical performance is a key step in the commercialization of intermediate-temperature solid oxide fuel cells (IT-SOFCs).

[0003] The prior art with publication number CN115863671A discloses a cathode material doped with Ca ions at the A site, a cathode strip, and a method for preparing a symmetrical battery. The maximum conductivity of the material described in the invention is 104.2S·cm -1 Although theoretically MIEC materials as IT-SOFC cathodes should have a conductivity greater than 100 S·cm -1 conductivity, but the material does not meet the above requirements within the actual operating temperature range of 600-800°C, limiting its application potential as a high-performance cathode material. In addition, power density is a key parameter for evaluating fuel cell performance and directly determines its practical application value. However, the invention did not test the power density of its material, lacking performance verification at the application level, which reduced its practicality and promotion value. Furthermore, if there is a significant TEC (thermal expansion coefficient) difference between the cathode and the electrolyte, large thermal stress will be generated at the interface, which can easily lead to the formation of microcracks and affect the structural stability and service life of the battery. Although the invention points out that the Fe-based material used has an appropriate TEC, it does not provide TEC test data for the cathode material after doping with Ca ions, so the effectiveness of its matching with the electrolyte remains to be verified.

[0004] Therefore, how to achieve the coordinated optimization of the electrical conductivity, thermal matching and electrochemical performance of solid oxide fuel cell cathode materials and solve the problem of low electrochemical performance of cathode materials and difficulty in using them under medium temperature conditions still needs further improvement. Summary of the Invention

[0005] The purpose of the present invention is to provide a method for preparing a B-site nickel-doped iron-based perovskite material and its application in medium-temperature solid oxide fuel cells to solve the above-mentioned problems in the background technology. The present invention successfully synthesized La with a single perovskite structure. 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ Cathode materials have high electrochemical properties and are more suitable for use as medium-temperature SOFC cathode materials.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide a B-site nickel-doped iron-based perovskite material for preparing a cathode of a solid oxide fuel cell, the chemical formula of which is La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ , where x is the Ni doping amount, 0<x≤0.2, and δ is the oxygen vacancy content, 0.2<δ≤0.3.

[0008] Preferably, the value of x is 0.1.

[0009] The second technical solution of the present invention is to provide a method for preparing the above-mentioned B-site nickel-doped iron-based perovskite material, which is prepared by an EDTA-CA sol-gel method, comprising the following steps:

[0010] Dissolving lanthanum salt, calcium salt, iron salt and nickel salt in water to obtain a metal ion solution; dissolving ethylenediaminetetraacetic acid (EDTA) in a solvent, then mixing with the metal ion solution and citric acid (CA), and adjusting the pH value to alkaline to obtain a precursor solution;

[0011] The precursor solution is heated and stirred until it becomes a viscous colloid, and then the solvent is evaporated to obtain a precursor powder, which is calcined to obtain the B-site nickel-doped iron-based perovskite material.

[0012] Preferably, the solvent is aqueous ammonia.

[0013] Preferably, the lanthanum salt is La(NO3)3; and / or the calcium salt is Ca(NO3)2; and / or the iron salt is Fe(NO3)3; and / or the nickel salt is Ni(NO3)2; and / or the molar ratio of the total molar amount of the iron salt and the nickel salt to the molar amount of the lanthanum salt and the calcium salt is 10:6:4, and the ratio of the molar amount of the nickel salt to the sum of the molar amounts of the iron salt and the nickel salt is 0-0.2 and is not 0.

[0014] Preferably, the molar ratio of the total molar amount of metal ions in the metal ion solution to CA and EDTA is 0.9-1.1:0.9-1.1:1.4-1.6.

[0015] Preferably, the pH value is 8.

[0016] Preferably, the method of heating and stirring the precursor solution until it becomes a viscous colloid and then evaporating and removing the solvent comprises the following steps: heating and stirring the precursor solution at 80° C. until it becomes a viscous colloid, and then heating it at 200° C. for 2 hours to obtain a fluffy, black precursor powder.

[0017] Preferably, the calcination treatment is performed at a temperature of 1000° C. and for a time of 5 hours; and / or the calcination treatment is performed in an air atmosphere.

[0018] The third technical solution of the present invention is to provide an application of the above-mentioned B-site nickel-doped iron-based perovskite material in the field of solid oxide fuel cell cathode materials.

[0019] A fourth technical solution of the present invention provides a solid oxide fuel cell, wherein the cathode material of the solid oxide fuel cell comprises the above-mentioned iron-based perovskite material doped with nickel at the B site.

[0020] The technical principles of the present invention are as follows:

[0021] The present invention uses EDTA dissolved in ammonia water for pretreatment. EDTA has poor solubility in acidic or neutral solutions. The alkaline environment provided by ammonia water can help dissolve EDTA better, facilitating subsequent complexation with metal ions. Furthermore, ammonia water is a weak base and easily volatilizes, allowing it to be completely removed during the subsequent heating step, preventing impurities from remaining and thus improving the purity of the final product.

[0022] During the preparation process, the ingredients were prepared using a molar ratio of n(total metal ions):n(CA):n(EDTA) = 0.9-1.1:0.9-1.1:1.4-1.6 (Group A). ​​To determine the optimal ratio, control experiments were conducted. EDTA, as a strong chelating agent, can form stable complexes with most metal ions. Adjusting the EDTA molar ratio to 0.9-1.1 (Group B) resulted in impure samples and the formation of NiO impurities. This is due to competitive complexation between metal ions, resulting in incomplete complexation. To ensure complete complexation of the metal ions, the EDTA molar ratio was increased to 1.9-2.1 (Group C). While this ensured sufficient complexation, it also led to new problems: coarsening of the sample particles and a significant increase in raw material costs. However, when the EDTA molar ratio was 1.4-1.5 (Group A), the experimental results were optimal, with no impurities formed and smaller particle size. Taking into account factors such as sample purity, performance and cost, the optimal molar ratio of EDTA was determined to be 1.4-1.6. This ratio can ensure sample quality while achieving rational utilization of resources.

[0023] As an auxiliary complexing agent, although CA has weaker complexing ability than EDTA, it can effectively regulate the gel formation rate of the system and prevent the uneven gel structure from affecting the final performance. When the CA molar ratio is adjusted to 0.4-0.6 (Group D), there is insufficient CA participating in the complexation reaction, resulting in the inability to completely complex the metal ions and the production of impurity NiO in the sample. When the CA molar ratio is adjusted to 1.4-1.6 (Group E), during high-temperature heat treatment, a large amount of residual CA decomposes to produce gas, which easily forms large pores inside the material, causing O2 to escape without sufficient reaction, reducing gas utilization. At the same time, the effective reaction area around the large pores drops sharply, resulting in a decrease in the activity of the oxygen reduction reaction. When the CA molar ratio is adjusted to 0.9-1.1 (Group A), this ratio helps to achieve a uniform distribution of metal ions, so that after calcination, a target perovskite material with high purity and no obvious agglomeration can be obtained. The present invention uses La 0.6 Ca 0.4 FeO 3-δ As the matrix material, Ni is used to 0.6 Ca 0.4 FeO 3-δ The B position of the doped La2O3 was doped, and the X-ray diffraction (XRD) results showed that La2O3 with a single perovskite structure was successfully synthesized. 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ For cathode materials, in addition to the peaks corresponding to the cathode and SDC electrolyte, no additional peaks were observed for all the materials studied, indicating that there was no chemical reaction between them and the SDC electrolyte and that they had good chemical compatibility.

[0024] In the process of preparing the precursor solution, the present invention adjusts the pH value of the reaction system to 8, which has the following three advantages: First, under alkaline conditions, the four carboxylic acid groups (-COOH) of EDTA are almost completely dissociated into carboxyl groups (-CO - ), can more effectively form stable soluble complexes with metal ions and avoid the formation of hydroxide precipitation. Secondly, the alkaline environment weakens the complexing effect of CA, making EDTA dominate the complexing reaction, thereby improving the stability of the complex. CA is more involved in the sol-gel transformation process, avoiding competition with EDTA for metal ions. Thirdly, the alkaline environment regulated by ammonia water helps to inhibit the premature hydrolysis of metal ions, enhance the stability and uniformity of the sol, and prevent phase separation or particle agglomeration in the gel stage. The EDS element distribution diagram shows that Ni has been successfully doped into La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ , and the La, Ca, Fe, Ni, and O elements are evenly distributed without obvious element segregation.

[0025] During the process of heating and stirring the precursor solution until it becomes a viscous colloid, heating it in an 80°C water bath with continuous stirring can effectively accelerate the rate of the complexation reaction and promote the full reaction between the complexing agent and the metal ions, thereby forming a uniform and stable precursor solution. This temperature condition can not only promote the complexation reaction, but also prevent the decomposition of the metal salt at high temperature. At the same time, the constant temperature provided by the water bath helps to evenly evaporate the water in the system. Combined with continuous stirring, it further prevents local overheating and the generation of concentration gradients, ensuring the composition and structural consistency of the product. In addition, controlling the water bath temperature at 80°C can effectively prevent the thermal decomposition of EDTA and CA, and avoid affecting the purity of the product due to carbon residue.

[0026] La of the present invention 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The material also has significant advantages in thermodynamic properties. The thermal expansion coefficient (TEC) is a key indicator for evaluating the thermal compatibility between electrode materials and electrolytes, and directly affects the structural stability of the long-term operation of intermediate-temperature solid oxide fuel cells (IT-SOFCs). 0.6 Ca 0.4 FeO 3-δ The TEC of the matrix material is 15.38×10 -6 K -1 , and when the Ni doping amount is x=0.2, La 0.6 Ca 0.4 Fe 0.8 Ni 0.2O 3-δ The TEC is 13.61×10 -6 K -1 It can be seen that the gradual doping of Ni significantly suppresses the thermal expansion behavior of the material, which helps to achieve matching with the commonly used electrolyte TEC, thereby improving the battery structural integrity and operating life.

[0027] The present invention dopes low-valent Ni ions at the B site, which will lead to Fe 3+ Oxidized to Fe 4+ To maintain La 0.6 Ca 0.4 Fe 1- x Ni x O 3-δ The electroneutrality of La increases with the increase of Ni doping amount. 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The conductivity of La 0.6 Ca 0.4 Fe 0.9 Ni 0.1 O 3-δ The maximum value (328.53S·cm) was reached at 500℃. -1 ), compared with the matrix (195.05S·cm -1 ), which increased by about 68.43%. This conductivity is much higher than the minimum standard required for IT-SOFC cathode materials (>100S·cm -1 ).

[0028] The beneficial technical effects of the present invention are as follows:

[0029] The present invention adopts EDTA-CA sol-gel method, uses EDTA and CA as complexing agents, and successfully synthesizes La with a single perovskite structure by doping Ni at the B position. 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ Cathode material. The product has good chemical compatibility and a porous microstructure.

[0030] The modification methods of the present invention greatly improve the electrochemical performance of the product, making it more suitable for use as a medium-temperature SOFC cathode material. 0.6 Ca 0.4 FeO 3-δ The conductivity of the product of the present invention is significantly improved, while the electrochemical impedance (Rp) is reduced, and the peak power density (PPD) reaches 674.62mW·cm at 800℃.-2 , which is 73.61% higher than that of the matrix. Ni doping reduces the TEC of the material, making it comparable to that of the SDC electrolyte (12.5×10 -6 K -1 ) to match the thermal expansion. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0032] Figure 1 The XRD spectra of the products of Example 1 and Comparative Examples 1-4 are shown.

[0033] Figure 2 The SEM images of the products of Example 1 and Comparative Examples 1-4 are shown in Figures a, b, c, d, and e, which are SEM images of the products of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4, respectively.

[0034] Figure 3 The XRD spectrum of the product of Example 1-2 and the XRD enlarged spectrum in the range of 32.0°≤2θ≤33.0° are shown in Figure 1-2. Wherein, a is the XRD spectrum and b is the XRD enlarged spectrum in the range of 32.0°≤2θ≤33.0°.

[0035] Figure 4 LCFN 0.1 |SDC||LCFN 0.1 XRD spectrum of .

[0036] Figure 5 a, b, c, d, and e are LCFN|SDC, LCFN 0.05 |SDC、LCFN 0.1 |SDC、LCFN 0.15 |SDC、LCFN 0.2 |SEM image of the cross section of SDC, f is LCFN 0.1 |SDC|SEM image of the cross section of NiO-SDC.

[0037] Figure 6The HR-TEM image and corresponding fast Fourier transform (FFT) pattern, and selected area electron diffraction (SAED) lattice fringe profile of the product of Example 1 are shown. In particular, a, c, and d are the HR-TEM image of the product on the d(110) crystal plane, the fast FFT pattern marked in a, and the SAED lattice fringe profile, respectively; b, e, and f are the HR-TEM image of the product on the d(100) crystal plane, the fast FFT pattern marked in b, and the SAED lattice fringe profile, respectively.

[0038] Figure 7 The STEM and EDS element distribution diagrams of the product of Example 1 are shown in Figure 1. Figure a is a STEM image, and figures b, c, d, e, and f are EDS element distribution diagrams.

[0039] Figure 8 This is the O1s spectrum of the product of Example 1-2.

[0040] Figure 9 Graph showing thermal expansion of the product of Example 1-2 from room temperature to 750°C.

[0041] Figure 10 The temperature variation diagram of the electrical conductivity of the product of Example 1-2 measured at 400-800°C.

[0042] Figure 11 The electrochemical impedance spectroscopy (EIS) diagram and the Arrhenius plot of polarization impedance versus temperature for the product of Example 3 measured at 600-800° C. are shown in Figures a, b, c, d, and e, respectively, and f is an Arrhenius plot.

[0043] Figure 12 This is a current density-voltage-power density (IVP) curve of the product of Example 4 measured at 600-800°C.

[0044] Where a is LCFN|SDC|NiO-SDC, b is LCFN 0.1 |SDC|NiO-SDC. DETAILED DESCRIPTION

[0045] Various exemplary embodiments of the present invention are now described in detail. This detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terms used in the present invention are only for describing specific embodiments and are not intended to limit the present invention.

[0046] In addition, for numerical ranges in the present invention, it is understood that each intervening value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any stated value or stated range, and any other stated value or intervening value in the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges may independently be included or excluded in the range.

[0047] Unless otherwise specified, all technical and scientific terms used herein have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention pertains. Although preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention. It should be noted that any details not described herein are conventional procedures in the art and are not the focus of the present invention.

[0048] The terms “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0049] In terms of material design strategies, A-site and B-site doping are common means to optimize the comprehensive performance of Fe-based perovskite materials. The present invention has found that doping low-valent cations at the A-site can release lattice oxygen through a charge compensation mechanism, thereby increasing the oxygen vacancy concentration and further enhancing oxygen ion conductivity. In contrast, doping low-valent cations at the B-site can induce changes in the valence state of Fe, forming small polaron hopping channels that are conducive to electron migration, significantly improving the electronic conductivity of the material. At the same time, Ni doping can effectively reduce the TEC of the material, making it better matched with the electrolyte, thereby improving interface stability and extending battery life. Ni 2+ / Ni 3 + The multivalent state characteristics of the material can also regulate the concentration of oxygen vacancies, further enhancing the catalytic activity of the material in ORR.

[0050] Therefore, the present invention proposes a preparation method of a B-site Ni-doped iron-based perovskite cathode material and its application in solid oxide fuel cells, aiming to achieve synergistic optimization of electrical conductivity, thermal matching and electrochemical performance, and solve the problem that Fe-based perovskite has low electrochemical performance and is difficult to use under medium temperature conditions.

[0051] Specifically, the present invention provides a B-site nickel-doped iron-based perovskite material for preparing a cathode of a solid oxide fuel cell, the chemical formula of which is La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ , where x is the Ni doping amount, 0<x≤0.2, and δ is the oxygen vacancy content, 0.2<δ≤0.3.

[0052] The present invention also provides a method for preparing the above-mentioned B-site nickel-doped iron-based perovskite material, which is prepared by an EDTA-CA sol-gel method and comprises the following steps:

[0053] (1) La(NO3)3·6H2O(AR), Ca(NO3)2·4H2O(AR), Fe(NO3)3·9H2O(AR) and Ni(NO3)2·6H2O(AR) are dissolved in water to obtain a metal ion solution; ethylenediaminetetraacetic acid (EDTA) is dissolved in ammonia water and then slowly added to the metal ion solution until it is completely dissolved, and then citric acid (CA) is added and stirred continuously until it is completely dissolved;

[0054] (2) adjusting the pH of the mixed solution obtained in step (1) to 8 by adding ammonia water under magnetic stirring;

[0055] (3) heating and stirring the mixed solution adjusted to pH 8 in step (2) in a constant temperature water bath at 80° C. until it becomes a viscous colloid;

[0056] (4) The viscous colloid in step (3) was placed in an evaporating dish and heated in a universal resistance furnace at 200°C for 2 h to obtain a fluffy black precursor powder;

[0057] (5) The fluffy black precursor powder in step (4) was placed in a crucible, calcined at 1000°C in a muffle furnace for 5 h, and cooled naturally to obtain La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ Cathode material.

[0058] Furthermore, the volume ratio of the EDTA to the ammonia water is 1:1.15, and the concentration of the ammonia water is 25%.

[0059] Furthermore, the molar ratio of the total molar amount of metal ions in the metal ion solution to citric acid and ethylenediaminetetraacetic acid is 0.9-1.1:0.9-1.1:1.4-1.6.

[0060] Furthermore, the high-temperature calcination is carried out in an air atmosphere.

[0061] The present invention also provides a solid oxide fuel cell, wherein the cathode material of the solid oxide fuel cell comprises the above-mentioned B-site doped nickel iron-based perovskite material.

[0062] The present invention also provides a method for testing the performance of the above-mentioned B-site nickel-doped iron-based perovskite material, comprising the following steps:

[0063] (1) Weigh 1.5 g of the above-mentioned B-site nickel-doped iron-based perovskite material in a mortar, add polyvinyl butyral (PVB) and anhydrous ethanol to grind it thoroughly, and after it is completely ground dry, put it into a mold, hold the pressure at 10 MPa for 2 minutes, press it into a rectangular strip, and then calcine it at 1200 ° C in a muffle furnace for 5 hours. Let it cool naturally to obtain a material for testing electrical conductivity and thermal expansion;

[0064] (2) Weigh 0.5 g of electrolyte cerium oxide (SDC) and place it in a circular mold. Maintain the pressure at 10 MPa for 2 min to form a circular SDC electrolyte sheet with a diameter of 15 mm. Calcinate it in a muffle furnace at 1450 °C for 10 h and cool it naturally to obtain a dense SDC electrolyte sheet.

[0065] (3) The above-mentioned B-site nickel-doped iron-based perovskite material was ball-milled for 1 hour and placed in an oven to dry; then it was mixed with terpineol and ethyl cellulose in a mass ratio of 100:94:6, and manually ground evenly to obtain a cathode slurry, which was then screen-printed on both sides of the above-mentioned SDC electrolyte sheet, placed in an oven and baked at 200°C for 12 hours, and then calcined in a muffle furnace at 1000°C for 2 hours. The material was naturally cooled to obtain a symmetrical battery for testing the polarization resistance of the material;

[0066] (4) NiO and SDC were mixed in a mass ratio of 6:4, and then the obtained NiO-SDC mixed powder was ball-milled with corn starch in a mass ratio of 4:1 for 24 hours to obtain a composite anode material NiO-SDC powder;

[0067] (5) The composite anode material NiO-SDC powder obtained in step (4) is placed in a circular mold, maintained at a pressure of 6 MPa for 1 min, pressed into a disc shape without demolding, and the electrolyte SDC is evenly spread on the disc, and the SDC is co-pressed on the top of the anode at a pressure of 10 MPa; the double-layer disc is calcined at 1450° C. in a muffle furnace for 5 h, and naturally cooled to obtain an anode sheet;

[0068] (6) The cathode slurry prepared in step (3) was printed on the electrolyte side of the above-mentioned anode sheet by screen printing, placed in an oven at 200°C for 12 hours, and then calcined in a muffle furnace at 1000°C for 2 hours. It was naturally cooled to obtain an anode-supported battery for testing the power density of the material.

[0069] Furthermore, the calcination operation during the preparation process is carried out in an air atmosphere.

[0070] Furthermore, the size of the rectangular strip sample in step (1) is 29.0 mm×6.0 mm×0.5 mm, and the mass ratio of the iron-based perovskite material doped with nickel at the B site to polyvinyl butyral is 50:1.

[0071] Furthermore, in step (2), when the circular SDC electrolyte sheet is calcined, it is carried out in a confined space, specifically, the circular SDC electrolyte sheet is sandwiched between two Al2O3 plates and then calcined.

[0072] Furthermore, the ball milling medium in step (3) and step (4) is anhydrous ethanol.

[0073] In step (1), polyvinyl butyral (PVB) is added as a binder. This binder can enhance the mechanical integrity of the rectangular strip structure during the press molding process, reduce the risk of sample fragmentation, and effectively inhibit the formation of cracks during the subsequent high-temperature calcination process. However, as an insulating material, its addition amount must be strictly controlled; in the raw material system of the present invention, if its addition amount exceeds a mass ratio of 50:1, it will block the ion or electron transmission path and reduce the electrochemical performance. This ratio (50:1) ensures the formation while also achieving sufficient decomposition of PVB during the calcination process, minimizing the negative impact of carbon residue on electrode performance.

[0074] In step (2), in order to prevent the circular SDC electrolyte sheet from warping or cracking due to uneven heating or inconsistent shrinkage during the high-temperature calcination process, the present invention adopts the method of placing the pressed electrolyte sheet between Al2O3 plates for restraint. The upper and lower Al2O3 plates are covered with the same size, which can apply uniform mechanical pressure during the calcination process, thereby ensuring the flatness of the sample morphology, improving its mechanical stability, and avoiding interference with subsequent performance tests due to warping or deformation. In addition, the Al2O3 plate is chemically inert and can effectively prevent it from reacting with the SDC electrolyte material. 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The SEM image of the cross section of the SDC electrolyte sheet shows that La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The cathode material and the SDC electrolyte sheet adhered tightly, and no obvious cracks were observed at the interface, indicating that the cathode material and the electrolyte had good interfacial bonding properties. 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The material has a porous microstructure, which is conducive to oxygen diffusion, surface oxygen exchange and charge conduction.

[0075] In step (3), the cathode slurry is prepared by mixing cathode material with pine oil and ethyl cellulose in a mass ratio of 100:94:6. As an organic solvent, pine oil gives the slurry appropriate viscosity and volatility, which is beneficial for uniform coating in the screen printing process. Ethyl cellulose has both thickening and bonding functions, which effectively improves the dispersion of the slurry and the uniformity of film formation. If the proportion of pine oil in the slurry is too high (such as rising to the same mass as the cathode, 100:100:6), the viscosity of the slurry is too high, which will increase the difficulty of printing and affect the quality of the film layer; if the proportion of ethyl cellulose is too high (such as 100:94:10), it may form an overly thick film layer after drying, increase the resistance to electron or ion transmission, and increase the residual carbon content after calcination, which will damage the electrode performance. La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ Electrochemical impedance spectroscopy (EIS) analysis measured at 600-800℃ showed that Ni doping reduced the Rp of the material from 0.16Ω·cm at 800℃ to 2 (La 0.6 Ca 0.4 FeO 3-δ ) is reduced to 0.097Ω·cm 2 (La 0.6 Ca 0.4 Fe 0.9 Ni 0.1 O 3-δ ), which improves the electrochemical performance of the battery.

[0076] In step (4), the present invention uses a mixed powder of NiO and SDC with a mass ratio of 6:4 to construct the anode functional layer to achieve the coordinated optimization of the electron and ion conduction paths. As an electrocatalyst, NiO not only provides an electronic conduction network, but also effectively promotes the electrochemical oxidation reaction of the fuel gas, while SDC provides excellent oxygen ion conductivity; the 6:4 ratio achieves a good balance between catalytic activity and ionic conductivity. In addition, in order to introduce a suitable pore structure to promote fuel gas transmission, corn starch with a mass ratio of 4:1 is further added to the NiO-SDC mixed powder as a pore former. During the high-temperature calcination process, corn starch can be thermally removed to form a through porous network, which significantly improves the gas diffusion performance of the anode layer. However, the amount of pore former needs to be precisely controlled: if the amount added is insufficient, the anode porosity will be too low and the gas transport will be limited; if the amount added is too much, the structure after sintering may be loose and the mechanical strength will be greatly reduced. In the present invention, the pore former accounts for 20% of the total mixed powder mass, achieving a good balance between pore formation efficiency and structural stability. From LCFN 0.1|SDC| The SEM image of the NiO-SDC cross section shows that the anode is loose and porous, which facilitates fuel gas transmission. The electrolyte is dense, effectively blocking direct contact between the anode and cathode sides, preventing short circuits.

[0077] The performance test results show that compared with undoped La 0.6 Ca 0.4 FeO 3-δ In comparison, when the Ni doping amount is x=0.1, the peak power density (PPD) at 800°C reaches 674.62 mW·cm -2 Compared with the matrix, PPD increased by 73.61%, significantly enhancing the overall output performance of SOFC.

[0078] The raw materials used in the following examples and comparative examples of the present invention are all commercially available products.

[0079] Example 1

[0080] A B-site nickel-doped iron-based perovskite material (chemical formula La 0.6 Ca 0.4 Fe 0.9 Ni 0.1 O 3-δ , the value of δ is 0.25), the steps are as follows:

[0081] (1) Taking the preparation of 5g of iron-based perovskite material as an example, the relative atomic mass of each element was consulted and its n was calculated to be 0.02457mol. Therefore, 6.3833g, 2.3208g, 8.9335g and 0.7145g of La(NO3)3·6H2O(AR), Ca(NO3)2·4H2O(AR), Fe(NO3)3·9H2O(AR) and Ni(NO3)2·6H2O(AR) were weighed in sequence and dissolved in 150ml of deionized water to obtain a metal ion solution. 21.5707g of EDTA(AR) was dissolved in 27.3mL of ammonia water (ammonia concentration was 25%) and then slowly added to the metal ion solution until it was completely dissolved. Then, 10.34055g of CA(AR) was added to the mixed solution and stirred continuously until it was completely dissolved.

[0082] (2) The mixed solution obtained in step (1) was adjusted to pH 8 by adding ammonia water under magnetic stirring.

[0083] (3) The mixed solution adjusted to pH 8 in step (2) was heated and stirred in a constant temperature water bath at 80° C. until it became a viscous colloid.

[0084] (4) The viscous colloid in step (3) was placed in an evaporating dish and heated in a universal resistance furnace at 200°C for 2 h to obtain a fluffy black precursor powder.

[0085] (5) The fluffy black precursor powder in step (4) was placed in a crucible, calcined in a muffle furnace at 1000°C for 5 h in an air environment, and cooled naturally to obtain La 0.6 Ca 0.4 Fe 0.9 Ni 0.1 O 3-δ Cathode material (denoted as LCFN 0.1 ).

[0086] Example 2

[0087] The only difference from Example 1 is that, when the total molar amount of metal ions remains unchanged, the molar ratio of Fe(NO3)3·9H2O(AR) to Ni(NO3)2·6H2O(AR) in the raw materials is changed from 0.9:0.1 to 0.95:0.05, 0.85:0.15, and 0.8:0.2, respectively, and compared with the treatment group in which Ni(NO3)2·6H2O(AR) is omitted and an equal molar amount of Fe(NO3)3·9H2O(AR) is added, the final products obtained are recorded as LCFN 0.05 、LCFN 0.15 、LCFN 0.2 、LCFN。

[0088] Comparative Example 1

[0089] The only difference from Example 1 is that the amount of EDTA is modified to 14.3805 g (denoted as n(total metal ions):n(CA):n(EDTA)=1:1:1).

[0090] Comparative Example 2

[0091] The only difference from Example 1 is that the amount of EDTA is modified to 28.7609 g (denoted as n(total metal ions):n(CA):n(EDTA)=1:1:2).

[0092] Comparative Example 3

[0093] The only difference from Example 1 is that the amount of CA is modified to 5.1703 g (denoted as n(total metal ions):n(CA):n(EDTA)=1:0.5:1.5).

[0094] Comparative Example 4

[0095] The only difference from Example 1 is that the amount of CA is modified to 15.5108 g (denoted as n(total metal ions):n(CA):n(EDTA)=1:1.5:1.5).

[0096] Example 3

[0097] A symmetrical battery, the preparation method is as follows:

[0098] 0.5 g of electrolyte samarium oxide-doped cerium oxide (SDC) was weighed and placed in a circular mold. The pressure was maintained at 10 MPa for 2 minutes to press into a circular SDC electrolyte sheet with a diameter of 15 mm. The sheet was calcined at 1450°C in a muffle furnace for 10 hours (during which the circular SDC electrolyte sheet was sandwiched between two Al2O3 plates to create a confined space). The sheet was cooled naturally to obtain a dense SDC electrolyte sheet.

[0099] The iron-based perovskite material doped with nickel at the B position of Example 1-2 was ball-milled with alcohol for 1 hour and dried in an oven; then it was mixed with terpineol and ethyl cellulose in a mass ratio of 100:94:6 and manually ground to obtain a cathode slurry, which was then screen-printed on both sides of the above-mentioned SDC electrolyte sheet, placed in an oven and baked at 200°C for 12 hours, and then calcined in a muffle furnace at 1000°C for 2 hours in an air environment and naturally cooled to obtain a symmetrical battery (when the product of Example 1 is added to the cathode slurry, the obtained symmetrical battery is recorded as LCFN 0.1 |SDC|LCFN 0.1 ; When LCFN is added 0.05 、LCFN 0.15 、LCFN 0.2 , LCFN, respectively, are recorded as LCFN 0.05 |SDC|LCFN 0.05 、LCFN 0.15 |SDC|LCFN 0.15 、LCFN 0.2 |SDC|LCFN 0.2 , LCFN|SDC|LCFN), used to test the polarization resistance of the material.

[0100] Example 4

[0101] An anode-supported battery, the preparation method is as follows:

[0102] NiO and SDC were mixed in a mass ratio of 6:4, and then the obtained NiO-SDC mixed powder and corn starch in a mass ratio of 4:1 were added with alcohol and ball-milled for 24 hours to obtain the composite anode material NiO-SDC powder.

[0103] 0.3 g of composite anode material NiO-SDC powder was placed in a circular mold, maintained at a pressure of 6 MPa for 1 min, pressed into a disc shape without demolding, 0.03 g of electrolyte SDC was evenly spread on the disc, and SDC was pressed on the top of the anode at a pressure of 10 MPa; the double-layer disc was calcined at 1450°C in a muffle furnace for 5 h and naturally cooled to obtain an anode sheet.

[0104] 2 g of the cathode slurry in Example 3 was printed on one side of the anode electrolyte by screen printing, baked in an oven at 200° C. for 12 h, and then calcined in a muffle furnace at 1000° C. for 2 h. The battery was naturally cooled to obtain an anode-supported battery (when the product of Example 1 was added to the cathode slurry, the obtained anode-supported battery was denoted as LCFN). 0.1 |SDC|NiO-SDC; when LCFN is added 0.05 、LCFN 0.15 、LCFN 0.2 , LCFN, respectively, are recorded as LCFN 0.05 |SDC|NiO-SDC、LCFN 0.15 |SDC|NiO-SDC、LCFN 0.2 |SDC|NiO-SDC, LCFN|SDC|NiO-SDC) to test the power density of the material.

[0105] Test Example 1

[0106] The materials used to test electrical conductivity and thermal expansion were prepared as follows:

[0107] 1.5 g of the iron-based perovskite material doped with nickel at the B site of Example 1 was weighed into a mortar, 0.03 g of polyvinyl butyral (PVB) and 10 mL of anhydrous ethanol were added and ground thoroughly. After being completely ground dry, it was placed in a mold and maintained at a pressure of 10 MPa for 2 minutes. It was pressed into a rectangular strip (size 29.0 mm × 6.0 mm × 0.5 mm), and then calcined in a muffle furnace at 1200°C for 5 hours and naturally cooled to obtain a material for testing electrical conductivity and thermal expansion.

[0108] Effect verification

[0109] 1. X-ray diffraction (XRD) characterization

[0110] Figure 1 The XRD spectra of the products of Example 1 and Comparative Examples 1-4 are shown.

[0111] Figure 1 In the figures, A, B, C, D and E represent the products of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, respectively.

[0112] Depend on Figure 1 As can be seen, the sample prepared by A (Example 1) has no impurities and is superior to Comparative Examples 1-4. B reduces the amount of EDTA (n(total metal ions):n(CA):n(EDTA)=1:1:1), and the sample is impure and produces impure NiO. This is because there is competitive complexation between metal ions, which leads to incomplete complexation. D reduces the amount of CA (n(total metal ions):n(CA):n(EDTA)=1:0.5:1.5), but insufficient CA participates in the complexation reaction, resulting in incomplete complexation of metal ions and the production of impurity NiO in the sample.

[0113] Figure 3 The XRD spectrum of the product of Example 1-2 and the XRD enlarged spectrum in the range of 32.0°≤2θ≤33.0° are shown in Figure 1-2. Wherein, a is the XRD spectrum and b is the XRD enlarged spectrum in the range of 32.0°≤2θ≤33.0°.

[0114] Depend on Figure 3 It can be seen that these materials have a single perovskite structure and no impurity peaks are detected. 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The XRD magnified spectrum in the range of 32.0°≤2θ≤33.0° shows that compared with La 0.6 Ca 0.4 FeO 3-δ (LCFN), Ni doping causes the (110) diffraction peak of perovskite to shift toward a large angle. This is because Oxidized to Partially replaced This also shows that Ni is successfully doped into La 0.6 Ca 0.4 FeO 3-δ lattice.

[0115] Figure 4 LCFN 0.1 |SDC||LCFN 0.1 XRD spectrum of .

[0116] Figure 4 In the 0.6 Ca 0.4 Fe 0.9 Ni 0.1 O 3-δ (LCFN 0.1 ) and SDC diffraction peaks, no other obvious multiple peaks were detected, indicating that LCFN 0.1 There is no chemical reaction between it and SDC, and it has good chemical compatibility.

[0117] 2. Scanning Electron Microscope (SEM) Characterization

[0118] Figure 2 The SEM images of the products of Example 1 and Comparative Examples 1-4 are shown in Figures a, b, c, d, and e, which are SEM images of the products of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4, respectively.

[0119] Depend on Figure 2 As can be seen, the product of Example 1 has a small particle size and a certain porosity, while the other control experiments all exhibit varying degrees of coarsening. Comparative Example 2, in which the amount of EDTA was increased (n(total metal ions):n(CA):n(EDTA) = 1:1:2), while ensuring sufficient complexation, presented a new problem: the sample exhibited particle coarsening and significantly increased raw material costs. Comparative Example 4, in which the amount of CA was increased (n(total metal ions):n(CA):n(EDTA) = 1:1.5:1.5), revealed that during high-temperature heat treatment, a large amount of residual CA decomposed to produce gas, which easily formed large pores within the material, allowing O2 to escape without sufficient reaction, reducing gas utilization. Simultaneously, the effective reaction area around the large pores decreased sharply, leading to a decrease in oxygen reduction reaction activity.

[0120] Figure 5 a, b, c, d, and e are LCFN|SDC, LCFN 0.05 |SDC、LCFN 0.1 |SDC、LCFN 0.15 |SDC、LCFN 0.2 |SEM image of the cross section of SDC, f is LCFN 0.1 |SDC|SEM image of the cross section of NiO-SDC.

[0121] Depend on Figure 5 It can be seen that La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The cathode material and the SDC electrolyte adhere closely, no obvious cracks are observed at the interface, and the SDC electrolyte sheet is dense. 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The material has a porous microstructure, which is a necessary condition for high electrode porosity and is conducive to oxygen diffusion, surface oxygen exchange and charge conduction.

[0122] 3. Transmission Electron Microscopy (TEM) Characterization

[0123] Figure 6The HR-TEM image and corresponding fast Fourier transform (FFT) pattern, and selected area electron diffraction (SAED) lattice fringe profile of the product of Example 1 are shown. In particular, a, c, and d are the HR-TEM image of the product on the d(110) crystal plane, the fast FFT pattern marked in a, and the SAED lattice fringe profile, respectively; b, e, and f are the HR-TEM image of the product on the d(100) crystal plane, the fast FFT pattern marked in b, and the SAED lattice fringe profile, respectively.

[0124] Depend on Figure 6 It can be observed that the lattice fringe spacing of 0.383 nm corresponds to the (100) crystal plane of perovskite, and the lattice fringe spacing of 0.272 nm corresponds to the (110) crystal plane of perovskite.

[0125] 4.TEM spectrum characterization

[0126] Figure 7 The STEM and EDS element distribution diagrams of the product of Example 1 are shown in Figure 1. Figure a is a STEM image, and figures b, c, d, e, and f are EDS element distribution diagrams.

[0127] Depend on Figure 7 It can be seen that La 0.6 Ca 0.4 Fe 0.9 Ni 0.1 O 3-δ Ni was successfully doped into the sample, and the La, Ca, Fe, Ni, and O elements were evenly distributed without obvious element segregation.

[0128] 5. X-ray Photoelectron Spectroscopy Characterization

[0129] Figure 8 This is the O1s spectrum of the product of Example 1-2.

[0130] Figure 8 Including adsorbed oxygen (O ads ), lattice oxygen (O lat ), vacancy oxygen (O vac ), moisture and oxygen (O moi ). Because O ads It is easy to desorb at high temperature to form oxygen vacancies, so O ads +O vac / O lat The ratio usually represents the oxygen vacancy concentration, which directly affects its electrochemical performance and stability. ads +O vac / O lat The ratios gradually increase, namely 1.41, 1.58, 1.74, 1.79, and 1.96.

[0131] 6. Thermal expansion test

[0132] Figure 9 Graph showing thermal expansion of the product of Example 1-2 from room temperature to 750°C.

[0133] For the long-term stability of SOFC performance, the thermal expansion compatibility of cathode materials and electrolytes is a key issue. It is usually necessary for adjacent components to have similar thermal expansion behavior to minimize thermal stress and cracking, thereby extending the life of the SOFC.

[0134] Figure 9 In, La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The thermal expansion of La is significantly lower than that of some common Co-based and Fe-based materials. 0.6 Ca 0.4 FeO 3-δ The TEC of the matrix material is 15.38×10 -6 K -1 , La 0.6 Ca 0.4 Fe 0.8 Ni 0.2 O 3-δ The TEC is 13.61×10 -6 K -1 It can be seen that the gradual doping of Ni significantly suppresses the thermal expansion behavior of the material, which helps to achieve matching with the commonly used electrolyte TEC, thereby improving the battery structural integrity and operating life.

[0135] 7. Rectangular strip conductivity test

[0136] Figure 10 The temperature variation diagram of the electrical conductivity of the product of Example 1-2 measured at 400-800°C.

[0137] Figure 10 In the case of Fe2O3, the conductivity increases with increasing temperature, showing semiconductor behavior. The carrier concentration and mobility increase with increasing temperature, resulting in increased conductivity. It reaches a maximum value at 500°C, after which the conductivity decreases with further increasing temperature, showing metal-like behavior. In order to maintain electrical neutrality, some Fe2O3 4+ Reduced to low-valent Fe 3+ At high temperatures, lattice vibration scattering is enhanced, carrier mobility is reduced, and at the same time, lattice oxygen is released to form oxygen vacancies at high temperatures. The formation of additional oxygen vacancies and the reduction of carrier mobility at higher temperatures are not conducive to the transport of electron holes, which leads to a decrease in conductivity. With the increase of Ni doping amount, La 0.6 Ca 0.4 Fe1-x Ni x O 3-δ The conductivity of the material gradually increases, La 0.6 Ca 0.4 Fe 0.9 Ni 0.1 O 3-δ It reaches its maximum value (328.5S·cm) at 500℃ -1 ). This is mainly because the present invention dopes low-valent Ni ions at the B site, which will lead to Fe 3+ Oxidized to Fe 4+ To maintain La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The electrical neutrality of LaO2 leads to the formation of oxygen vacancies, thereby improving the conductivity. However, it does not mean that doping more Ni is more conducive to electron-hole transport. The formation of excessive oxygen vacancies will reduce the migration ability of electron holes. When the Ni doping is 0.2, the conductivity is significantly lower than that of undoped LaO2. 0.6 Ca 0.4 FeO 3-δ .

[0138] 8. Symmetrical battery electrochemical impedance test

[0139] Figure 11 The electrochemical impedance spectroscopy (EIS) diagram and the Arrhenius plot of polarization impedance versus temperature for the product of Example 3 measured at 600-800° C. are shown in Figures a, b, c, d, and e, respectively, and f is an Arrhenius plot.

[0140] Figure 11 In, LCFN, LCFN 0.05 、LCFN 0.1 、LCFN 0.15 、LCFN 0.2 Represent LCFN|SDC|LCFN, LCFN 0.05 |SDC|LCFN 0.05 、LCFN 0.1 |SDC|LCFN 0.1 、LCFN 0.15 |SDC|LCFN 0.15 、LCFN 0.2 |SDC|LCFN 0.2 .

[0141] Depend on Figure 11 It can be seen that Ni doping reduces the Rp of the material from 0.16Ω·cm at 800℃ 2 (La 0.6 Ca0.4 FeO 3-δ ) is reduced to 0.097Ω·cm 2 (La 0.6 Ca 0.4 Fe 0.9 Ni 0.1 O 3-δ ), which improves the electrochemical performance of the battery. With the increase of Ni doping amount, Rp shows a trend of first decreasing and then increasing. This is because excessive doping may cause oxygen vacancies to be localized, hindering the migration of oxygen ions. According to the slope of the Arrhenius curve, La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ The activation energies are 1.188ev, 1.137ev, 0.966ev, 0.952ev, and 0.955ev, respectively. 0.6 Ca 0.4 Fe 0.85 Ni 0.15 O 3-δ has the lowest activation energy.

[0142] 9. Anode-supported battery power density test

[0143] Figure 12 This is a current density-voltage-power density (IVP) curve of the product of Example 4 measured at 600-800°C.

[0144] Where a is LCFN|SDC|NiO-SDC, b is LCFN 0.1 |SDC|NiO-SDC.

[0145] Figure 12 In the case of undoped La 0.6 Ca 0.4 FeO 3-δ Compared with (LCFN|SDC|NiO-SDC), when Ni doping was 0.1 (Example 1), PPD reached 674.62 mW·cm at 800°C. -2 , compared with the matrix, PPD increased by 73.61%.

[0146] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.

Claims

1. A B-site nickel-doped iron-based perovskite material for preparing a solid oxide fuel cell cathode, characterized in that: The chemical formula is La 0.6 Ca 0.4 Fe 1-x Ni x O 3-δ , where 0<x≤0.2, 0.2<δ≤0.

3.

2. The iron-based perovskite material according to claim 1, characterized in that The value of x is 0.

1.

3. A method for preparing the B-site nickel-doped iron-based perovskite material according to claim 1 or 2, characterized in that: The following steps are involved: Dissolving lanthanum salt, calcium salt, iron salt and nickel salt in water to obtain a metal ion solution; dissolving ethylenediaminetetraacetic acid in a solvent, then mixing with the metal ion solution and citric acid, and adjusting the pH value to alkaline to obtain a precursor solution; The precursor solution is heated and stirred until it becomes a viscous colloid, and then the solvent is evaporated to obtain a precursor powder, which is calcined to obtain the B-site nickel-doped iron-based perovskite material.

4. The preparation method according to claim 3, characterized in that The lanthanum salt is La(NO3)3; and / or the calcium salt is Ca(NO3)2; and / or the iron salt is Fe(NO3)3; and / or the nickel salt is Ni(NO3)2; and / or the molar ratio of the total molar amount of the iron salt and the nickel salt to the molar amount of the lanthanum salt and the calcium salt is 10:6:4, and the ratio of the molar amount of the nickel salt to the sum of the molar amounts of the iron salt and the nickel salt is 0-0.2 and is not 0.

5. The preparation method according to claim 3, characterized in that The molar ratio of the total molar amount of metal ions in the metal ion solution to citric acid and ethylenediaminetetraacetic acid is 0.9-1.1:0.9-1.1:1.4-1.

6.

6. The preparation method according to claim 3, characterized in that The pH value is 8.

7. The preparation method according to claim 3, characterized in that The method of heating and stirring the precursor solution until it becomes a viscous colloid and then evaporating and removing the solvent comprises the following steps: heating and stirring the precursor solution at 80° C. until it becomes a viscous colloid, and then heating at 200° C. for 2 hours to obtain a fluffy, black precursor powder.

8. The preparation method according to claim 3, characterized in that The calcination treatment is performed at a temperature of 1000° C. and for a time of 5 hours; and / or the calcination treatment is performed in an air atmosphere.

9. Use of the B-site nickel-doped iron-based perovskite material according to claim 1 or 2 in the field of solid oxide fuel cell cathode materials.

10. A solid oxide fuel cell, characterized in that: The cathode material of the solid oxide fuel cell comprises the B-site nickel-doped iron-based perovskite material according to claim 1 or 2.

Citation Information

Cited By

  • Preparation and application of intermediate-temperature solid oxide fuel cell cathode material for improving Sm &lt; 0.5 &gt; Sr &lt; 0.5 &gt; FeO &lt; 3-delta &gt; oxygen reduction activity through B-site regulation

    CN121123301A